The Influence of Socioeconomic Factors and Religiosity on Religious Tolerance Among Students at Indonesian Islamic Higher Education Institutions - Zulkifli Zulkifli; Rena Latifa; Muhamad Fahri; Sholikatus Sa’diyah (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
Religious tolerance is fundamental to establishing religious moderation and harmonious life, a critical issue that has garnered considerable attention from researchers and academics in Indonesia. Understanding tolerance requires considering various factors that shape and influence it beyond simple faith dimensions. This study investigates the influence of specific socioeconomic factors and personal religiosity on the religious tolerance levels among Muslim students attending Indonesia’s State Islamic Higher Educational Institutions (PTKIN). Employing a quantitative approach, the research utilizes multiple regression analysis to examine the relative contributions of the independent variables (socioeconomic factors and religiosity) toward religious tolerance. The findings indicate that three out of four socioeconomic aspects, gender, organizational affiliation, and parental income, significantly affect students’ religious tolerance. Conversely, the amount of allowance received was not found to be a significant predictor of tolerance. Crucially, the students’ self-reported personal religiosity did not significantly influence their religious tolerance scores. This suggests that tolerance among PTKIN students is not explained by their individual depth of religious observance or piety level. The study implies that promoting effective religious tolerance within Islamic educational contexts should prioritize strategies that enhance social and economic exposure, particularly through engaging organizational and diverse university-level social activities, rather than focusing solely on increasing religious instruction.